Peran Organasi Remaja Masjid dalam Membentuk Generasi Muda - Muhamad Ridwan (Fakultas Tarbiyah Dan Ilmu Keguruan Institut Agama Islam An-Nawawi Purworejo, 2023)
Adolescents are the successor generation for the nation’s future. They become a benchmark for a successful and advanced nation. Therefore, this study aims to find out several teenagers’ activities which can pass on the leadership to young generation This research uses qualitative method with case study approach, the data collected through direct interview with ten informants (college students) by using a purposive sampling technique. To strengthen interview data, the writer performed passive participation observation by coming directly to the observed location. All results of the interview were analyzed using Milles and Hauberman’s pattern. Overall, the results of the analysis show three activities of the Youth Masjid Activist program in shaping the young generations. They are i) motivational training, ii) religious mentoring, and iii) group discussions. The results of this research can be used as initial data for future research investigating similar problems in different contexts and issues.